Shining a Brighter Light: Comprehensive Evidence on Adoption and Diffusion of CGIAR-related Innovations in Ethiopia - Kosmowski, Frederic; Alemu, Solomon; Mallia, Paola; Stevenson, James R.; Macours, Karen (CGIAR Advisory Services, 2020)
SPIA has developed a comprehensive, country-level approach to documenting the adoption and diffusion of agricultural innovations linked to CGIAR research. The first focal country for this approach is Ethiopia, where SPIA has been working since 2015.